How to measure intensity during on-water sprint kayaking? - de Zee, M.; Kristiansen, M.; Lauridsen, H. B.; Klitgaard, K. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: In cycling the use of power meters is the most used way to assess the intensity of the athlete. It is an objective measure of intensity, and it is not dependent of the slope and/or weather conditions. The measurement of power is relatively easy and mechanically transparent. However, the measurement of power in on-water sprint kayaking is actually very complicated. The reason is that for measuring power you need a force and a velocity. The force one could get from an instrumented paddle, but the question remains which velocity to take and at the same time make sure that the calculated power output is independent from for example wind conditions. In this work, we present therefore an alternative method to calculate the intensity of a kayaking athlete using impulse based on measured paddle forces.